Rationality and Creativity Interplay in Research by Design as Seen from the Inside - Harahap, M. Mirza Y.; Tregloan, Kate; Nervegna, Anna (UI Scholars Hub, 2019)
While research by design is critical in the development of architecture and design knowledge, there is still a need to deeply understand the design knowledge about the interplay between rationality and creativity in research-by-design projects. This paper attempts to address this issue by illustrating, rather than conceptualising, the inside process of a research by design project. The inside process will be discussed from three different points of view: (1) research or design interest tendency, (2) the performance of reflective attitude, and (3) a combination of views (1) and (2). The study resulted in an illustration of the interplay that suggests a dynamic forward-backwards act of thinking and making of a research-by-design project.